2019
DOI: 10.1186/s13018-019-1502-5
|View full text |Cite
|
Sign up to set email alerts
|

The appropriate hybrid surgical strategy in three-level cervical degenerative disc disease: a finite element analysis

Abstract: ObjectiveThe purpose of this FE study was to analyze the biomechanical characteristics of different HS strategies used in the treatment of three-level CDDD (one-level CDA and two-level ACDF).MethodsWe validated the FE model of an intact cervical spine established by transferring the data, collected by 3D CT scan, to the FE software ABAQUS and comparing these data with the data from published studies. Then, the FE model of hybrid surgery was reconstructed to analyze the range of motion (ROM), facet joint force,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…They found that the CDA-CDA-ACDF construct may lead to more compensation in terms of motion and facet stress. The biomechanical differences of three-level HS concerning one-level CDA and two-level ACDF was employed in Xie et al [ 12 ] study. The results showed that the ACDF-CDA-ACDF construct resulted in a better theoretical outcome, especially in preserving the maximum total ROM.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the CDA-CDA-ACDF construct may lead to more compensation in terms of motion and facet stress. The biomechanical differences of three-level HS concerning one-level CDA and two-level ACDF was employed in Xie et al [ 12 ] study. The results showed that the ACDF-CDA-ACDF construct resulted in a better theoretical outcome, especially in preserving the maximum total ROM.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison and analysis of the biomechanical changes in the nine surgical models will aid in the selection of an appropriate surgical plan in clinical practice. Previous biomechanical studies have assessed the interbody fusion cage contact pressure, endplate contact pressure, titanium plate and screw contact pressure, and displacement of the cervical vertebrae [ 13 , 22 24 ]. However, the biomechanical characteristics of the cervical spine after various anterior cervical surgeries have not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The element types and material properties used in the FE model were defined according to previous reports 22 25 and are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…A total of seven ligaments were modeled, including the anterior longitudinal ligament, posterior longitudinal ligament, ligamentum flavum, capsular ligament, interspinous ligament, supraspinous ligament, and intertransverse ligament. The element types and material properties used in the FE model were defined according to previous reports [22][23][24][25] and are shown in Table 1.…”
Section: Fe Modelingmentioning
confidence: 99%
See 1 more Smart Citation